2014
DOI: 10.1556/aphysiol.101.2014.3.11
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omega-3 on cognition in hypothyroid adult male rats

Abstract: Thyroid hormones and omega-3 are essential for normal brain functions. Recent studies have suggested that omega-3 may protect against the risk of dementia. The aim of this study was to investigate the effect of hypothyroidism on spatial learning and memory in adult male rats, the underlying mechanisms and the possible therapeutic value of omega-3 supplementation. Thirty male rats were divided into three groups; control, hypothyroid and omega-3 treated. Hypothyroidism induced significant deficits in working and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
2
10
1
Order By: Relevance
“…Also, the Serotonin level in the other experimental groups remained unchanged with the control group. These observations are in support of the study carried out by Abd Allah, 29 who reported a similar effect in his study on omega-3 fatty acids. Glutathione level was significantly high in the Group 2 and 3 animals (26.32 ± 7.09 and 26.04 ± 7.22 µmol/L, respectively) in comparison with the control group (10.01 ± 2.12 µmol/L).…”
Section: Effect Of Omega-3 Oil On Biochemical Parameters In Blood Serum Of Experimental Rabbitssupporting
confidence: 91%
“…Also, the Serotonin level in the other experimental groups remained unchanged with the control group. These observations are in support of the study carried out by Abd Allah, 29 who reported a similar effect in his study on omega-3 fatty acids. Glutathione level was significantly high in the Group 2 and 3 animals (26.32 ± 7.09 and 26.04 ± 7.22 µmol/L, respectively) in comparison with the control group (10.01 ± 2.12 µmol/L).…”
Section: Effect Of Omega-3 Oil On Biochemical Parameters In Blood Serum Of Experimental Rabbitssupporting
confidence: 91%
“…The potential role of DHA and EPA in the prevention of cognitive decline, including the decline associated with AD, has attracted major interest over the past 20 years. Recent research showed that n-3 fatty acids supplementation ameliorated memory deficits, which increased the serum total antioxidant capacity [ 118 ]. On the other hand, EPA and DHA supplementation for 2 years was not found to affect the cognitive decline in healthy elderly individuals [ 119 ].…”
Section: Nutrients In Microglia Aging and Cognitive Functionmentioning
confidence: 99%
“…ω-3 FAs supplementation improved memory deficits, increased serum total antioxidant capacity, and also a diminished expression of Cav1.2 protein (the voltage dependent LTCC alpha 1c subunit), together with reduced structural changes, were observed. The data showed that ω-3 FAs could be a useful neuroprotective agent against the cognitive damage that hypothyroidism can induce [43].…”
Section: Omega-3 Polyunsaturated Fatty Acids (Or Fish Oil)mentioning
confidence: 95%
“…Another study investigated in adult male rats the effect of hypothyroidism on spatial learning and memory, the underlying mechanisms and the potential therapeutic role of ω-3 supplementation [43]. A subdivision into 3 groups was done starting from 30 male rats: Control, hypothyroid and ω-3 treated.…”
Section: Omega-3 Polyunsaturated Fatty Acids (Or Fish Oil)mentioning
confidence: 99%